2011
DOI: 10.1111/j.1526-100x.2010.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of the Restoration Capacity of a Fish‐Farm Impacted Area with Posidonia oceanica (L.) Delile Seedlings

Abstract: Marine aquaculture is an activity that has induced severe local losses of seagrass meadows along the coastal areas. The purpose of this study was to evaluate the capacity of an area degraded by fish-farm activities to support Posidonia oceanica seedlings. In the study site, a bay in the southeast coast of Spain where part of a meadow disappeared by fishfarm activities, seedlings inside mesh-pots were planted in three areas. Two plots were established in each area, one in P. oceanica dead matte and another insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…But, a change in the topography of sea floor due to physical disturbance, in particular the formation of erosion channels created by elevated levels of turbulence within the patches during severe storms, might have played a role. Even though high herbivore consumption rates of fruits/seeds have been reported ( Balestri and Cinelli, 2003 ) and bite marks on leaves were found on transplanted seedlings of P. oceanica ( Domínguez et al, 2012 ), herbivore pressure did not appear to be a threat for early life stages. However, our observations revealed that the sea urchin P. lividus , one of the major consumers of P. oceanica fruits, may cover itself with detached seedlings.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…But, a change in the topography of sea floor due to physical disturbance, in particular the formation of erosion channels created by elevated levels of turbulence within the patches during severe storms, might have played a role. Even though high herbivore consumption rates of fruits/seeds have been reported ( Balestri and Cinelli, 2003 ) and bite marks on leaves were found on transplanted seedlings of P. oceanica ( Domínguez et al, 2012 ), herbivore pressure did not appear to be a threat for early life stages. However, our observations revealed that the sea urchin P. lividus , one of the major consumers of P. oceanica fruits, may cover itself with detached seedlings.…”
Section: Discussionmentioning
confidence: 91%
“…Seedlings are increasingly an important management tool for seagrass restoration, and studies have shown that cultivated seedlings of P. oceanica can be transplanted in the field with relatively high success and thus used as planting material for assisted colonization at shallow sites or for restoration of small damaged areas in disturbed meadows ( Balestri et al, 1998b ; Domínguez et al, 2012 ; Terrados et al, 2013 ). Since stranded P. oceanica fruits are increasingly available in many countries, they may be planted in selected suitable areas to create reservoirs of juveniles for future restoration activities.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the local management of fishing and anchoring inside the MPA seems to provide some insurance against large-scale pressures, such as sedimentation, which are impractical to manage directly. Montefalcone et al [78] conclude that MPAs alone are not sufficient to guarantee the protection of P. oceanica meadows and that management tools other than MPAs are needed to enhance the large-scale persistence of this habitat [79] , [80] . Activities that reduce coastal pollution and eutrophication by the establishment of management plans for water resources, for instance, are also key elements for the recovery of habitats such as Cystoseira spp.…”
Section: Discussionmentioning
confidence: 99%
“…priority [18] and many experimental restoration projects [19][20][21][22][23][24][25] or finalized to the active restoration of degraded areas [26,27] have been performed. A wide range of techniques have been used, such as grids, concrete frames, and metal sticks, to anchor vegetative shoots [20,24,28,29].…”
Section: Methodsmentioning
confidence: 99%
“…In the Mediterranean Sea, most restoration efforts have been addressed to the endemic seagrass Posidonia oceanica (L.) Delile, due to the extension and ecological role of its meadows [17]. Conservation of P. oceanica meadows is a national and international Water 2021, 13, 661 2 of 10 priority [18] and many experimental restoration projects [19][20][21][22][23][24][25] or finalized to the active restoration of degraded areas [26,27] have been performed. A wide range of techniques have been used, such as grids, concrete frames, and metal sticks, to anchor vegetative shoots [20,24,28,29].…”
Section: Introductionmentioning
confidence: 99%